2014
DOI: 10.1111/jgh.12775
|View full text |Cite
|
Sign up to set email alerts
|

Acetic acid induces cell death: An in vitro study using normal rat gastric mucosal cell line and rat and human gastric cancer and mesothelioma cell lines

Abstract: Background and Aim: We recently reported that topical application of acetic acid promptly caused tumor necrosis in a mouse model of gastric cancer. The aim of the present study was to examine whether acetic acid can directly induce cancer cell death. Methods: Rat gastric epithelial cell line (RGM-1), rat gastric carcinoma cell line (RGK-1), human gastric cancer cell line (KATO III), and human mesothelioma cell lines (ACC-MESO1 and MSTO-211H) were used. Acetic acid was added into the cell culture at different c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 27 publications
(56 reference statements)
1
12
0
Order By: Relevance
“…Briefly, L929 cell lines were cultured in Dulbecco's Modified Eagle's Medium (Himedia, India) supplemented with 10% fetal bovine serum, streptomycin (0.1 mg/mL) and penicillin (100 U/mL) and maintained at 37˚C, 5% CO 2 . Cells were seeded in microtitre plate at a density of 10 4 cells/mL and incubated for 24 h. The cells were then treated with acetic acid concentrations ranging from 0.039-5% for 2.5, 5, 7.5 and 10 min, immediately followed by aspiration and replacement with fresh medium [26]. After 24 h of incubation, the medium was aspirated and MTT assay was performed as described above.…”
Section: Cytoxicity Of Acetic Acid Against L929 Mouse Fibroblast Cell Linementioning
confidence: 99%
“…Briefly, L929 cell lines were cultured in Dulbecco's Modified Eagle's Medium (Himedia, India) supplemented with 10% fetal bovine serum, streptomycin (0.1 mg/mL) and penicillin (100 U/mL) and maintained at 37˚C, 5% CO 2 . Cells were seeded in microtitre plate at a density of 10 4 cells/mL and incubated for 24 h. The cells were then treated with acetic acid concentrations ranging from 0.039-5% for 2.5, 5, 7.5 and 10 min, immediately followed by aspiration and replacement with fresh medium [26]. After 24 h of incubation, the medium was aspirated and MTT assay was performed as described above.…”
Section: Cytoxicity Of Acetic Acid Against L929 Mouse Fibroblast Cell Linementioning
confidence: 99%
“…The clinical-grade silicone showed an increased cell apoptosis when incubated with the mammalian fibroblast cell line, and this was attributed to the underlying substrate toxicity as a result of the use of acetic acid in the curing process. As found by Okabe et al (2014), the use of acetic acid in mammalian cell culture induces cell death and apoptosis. As a result, any effect of the polymer calixarene polymer coating on this substrate was masked.…”
Section: Discussionmentioning
confidence: 85%
“…As found by Okabe et al . (), the use of acetic acid in mammalian cell culture induces cell death and apoptosis. As a result, any effect of the polymer calixarene polymer coating on this substrate was masked.…”
Section: Discussionmentioning
confidence: 99%
“…( 15 ) Notably, 0.1% and 0.01% acetic acid in culture medium results in pH values of 6.8 and 7.4, respectively. ( 6 ) Additionally, 5 µM acetic acid is lower than 0.01%, and the pH of the solution remains approximately 7.4. Thus, the cytotoxic effects of acetic acid are not related to pH.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in a previous study, we reported that 0.5 vol% acetic acid induced cell death, particularly in cancer cells. ( 6 ) In contrast, 60 vol% acetic acid causes cellular necrosis and ulcers following topical treatment. ( 7 ) These data indicated that the cytotoxic effects of acetic acid depend on the concentration of the chemical.…”
Section: Introductionmentioning
confidence: 99%